ON BOUNDEDNESS AND COMPLETE POSITIVITY OF MAPS ON BANACH ALGEBRAS - Okelo, N. B. (Journal of Global Research in Mathematical Archives(JGRMA), 2017)
Let and be algebras, and be by matrices with entries from and respectively and be a linear map, then we define maps by for all natural numbers . We determine conditions under which is positive for all Keywords: Hermitian maps, unital -homomorphism and completely positive maps.